The Lithosphere‐Asthenosphere System Beneath the North Atlantic and Surroundings: Results From Multi‐Observable Probabilistic Inversions - Farshad Salajegheh; Juan Carlos Afonso; Alexander Minakov; Parviz Ajourlou; Carmen Gaina; Olga Ortega‐Gelabert (Geochemistry, Geophysics, Geosystems)
Abstract The North Atlantic region is a complex geodynamic setting that comprises multiple continental blocks, sedimentary basins, mid‐ocean ridge systems and prominent hotspots. Recent geophysical surveys of the near‐surface have enhanced our understanding of crustal elements and the shallow lithosphere. However, our knowledge of the deep lithospheric structure and the physical state and dynamics of the upper mantle is still limited. Here, we exploit the combined sensitivity of surface‐wave data, geoid anomalies, absolute topography and surface heat flow to obtain full thermochemical models of the region from the surface down to 350 km. We jointly invert these data sets using a simulation‐based, multi‐observable probabilistic framework. We validate our results with independent thermobarometric and chemical information from mantle xenoliths and test the effects of using different seismic models on the inversion results. Our model reveals an intricate sublithospheric flow system, driven by the interaction of deep upwellings with the highly irregular lithospheric structure. We corroborate that the main thermal anomaly in the sublithospheric mantle shows a tilted geometry, moving toward Greenland with depth. We reveal that this large‐scale anomaly transition into a more complex pattern once it reaches depths of ∼150 km beneath the North Atlantic. Small‐scale downwellings originate from the margins of continental domains, resulting in a complex circulation pattern that limits the radial spread of the deep upwellings and preferentially focuses them within regions of thin lithosphere along a N–S direction. Distinct compositional anomalies in the Greenland lithosphere delineate the North Atlantic Craton, the Nagssugtoqidian mobile belt, and the covered remnants of the Disko Craton. In continental Europe, the East European Craton shows clear indications of depletion in incompatible elements, with the Kola‐Karelian cratonic region showing the highest levels of depletion. Our model serves as a base to make interpretations on the enigmatic paleotectonic history of the North‐Atlantic region.